Encoding dot-like events in Modern Standard Chinese. (July 2017) - Cominetti, Federica; Simone, Raffaele
Abstract: This paper investigates which nominal strategies are available in a language to encode the dot-like process, i.e., the one described by the features [−durative, +telic]. A variety of solutions is available: clausal, phrasal and lexical. The language taken into consideration is Modern Standard Chinese, where lexical and phrasal solutions are used, both interestingly involving a characteristic use of classifiers. Three (plus one) different types of lexicalizations are identified for the encoding of dot-like processes in Chinese. The paper also suggests an affinity between such nominals and classifiers and corroborates the claim that operations such as nominalization spread through typologically different languages. Highlights: Dot-like events may get specific encoding on the verb-noun continuum. Encoding strategies for dot-like events may be lexical, morphological or phrasal. Chinese has specific strategies for encoding dot-like events. Such strategies are of two kinds: lexical and phrasal. All the strategies for encoding dot-like events in Chinese involve the use of a classifier.